Flow and aggregation of rod-like proteins in slit and cylindrical pores coated with polymer brushes: an insight from dissipative particle dynamics. Issue 8 (30th January 2017) - Posel, Zbyšek; Svoboda, Martin; Colina, Coray M.; Lísal, Martin
Abstract : We use a meso-scale dissipative particle dynamics method to simulate the flow and aggregation of rod-like protein solutions through pores grafted with a solvent-sensitive polymer brush. Abstract : We use a meso-scale dissipative particle dynamics method to simulate the flow and aggregation of rod-like protein solutions through pores grafted with a solvent-sensitive polymer brush. The coated pores can control protein permeability and aggregation by a stretch-to-collapse conformational transition of the brush polymers in response to changes in the solvent quality. The protein solutions mimic aqueous glycoprotein solutions and proteins are represented as rod-like objects formed by coarse-grain beads. The model further employs two types of beads to represent the existence of cystein-like terminal groups in real glycoproteins and mimic the aggregation of real glycoproteins in aqueous solutions. We vary the solvent quality with respect to the brush chains and study the flow and aggregation of rod-like proteins in the slit and cylindrical pores as the brush polymers undergo the stretch-to-collapse transition. The results show that stretched brush chains close the pore, hamper proteins' flow and promote proteins' aggregation. The collapsed brush chains open the pores for proteins' flow and suppress their aggregation. Therefore, we observe more than a ten-fold reduction in the permeation rate of proteins in both pore geometries. Finally, due to pore confinement, larger proteins' aggregates are formed in the slit pore than in the cylindrical pore, while more pronounced orientation of proteins in the flow direction is seen in the cylindrical pore than in the slit pore.